The Effect of Occupational Health and Safety (OHS) Knowledge and Heavy Equipment Maintenance in Coal Bulk Carrier Loading–Unloading Operations on Hazard Control and Its Implications for Work Safety at PT Puradika Bongkar Muat Makmur, Taboneo Sea, South Kalimantan - Rony Kurnia; Abdul Rachman; Marihot Simanjuntak; Susi Herawati (Dinasti International Journal of Management Science, 2026)
Loading and unloading activities involve a high risk of accidents, particularly in the operation of wheel loaders, bulldozers, and ship cranes, thus requiring strengthened occupational safety and health (OSH/K3) competence and optimal equipment maintenance. This study aims to examine and analyze the effect of OSH knowledge and heavy equipment maintenance for ship-based loading and unloading on hazard control and its implications for occupational safety at the work area of PT Puradika Bongkar Muat Makmur Laut Taboneo, South Kalimantan. The study employed a quantitative approach with a cross-sectional design. The population consisted of 53 wheel loader and bulldozer operators (organic employees) and 50 ship crane operators (subcontract workers), totaling 103 respondents using a total sampling technique. Data were collected through questionnaires and OSH report documentation, and analyzed using SmartPLS. The results indicate that OSH knowledge and heavy equipment maintenance have a positive and significant effect on hazard control, with equipment maintenance showing the most dominant influence. Furthermore, OSH knowledge, equipment maintenance, and hazard control have positive and significant effects on occupational safety, both directly and indirectly through hazard control as a mediating variable. These findings highlight that improved risk understanding, effective condition monitoring, and the implementation of technical controls contribute to reducing workplace accident potential in loading and unloading operations. The study recommends enhancing emergency response training through simulation-based programs, strengthening digital-based spare parts management systems, and optimizing engineering controls in the work area to minimize risks. In addition, reinforcing behavior-based safety programs and conducting periodic safety evaluations are essential to reduce accident rates and property damage. These strategies are expected to improve occupational safety performance in a sustainable manner.